2021
DOI: 10.3126/ijssm.v8i1.32694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pesticide Application Pattern in Major Vegetables of Palpa District, Nepal

Abstract: This study was conducted to determine the cost contribution of pesticide to total cost of vegetable production along with criteria for the choice of pesticides, its handling and application pattern. It also includes the amount of pesticides imported in 2020 in Palpa district. Fifty farmers and 15 agro-vets were selected for a pretested questionnaire schedule. Microsoft-Excel and Statistical Package for Social Sciences were used to analyze the data. Mean and standard deviation was used to categorize the age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A study conducted in Palpa, Nepal observed that only 6% of farmers took complete protective measures like wearing protective clothing, hand gloves, goggles, masks, and taking bath immediately after application. (13) The findings from Bakhsh and colleagues another study in Pakistan on cotton farm workers revealed similar results as 40% young and 68% elder cotton pickers did not comply with safety measures. (23) In Egypt more than 97% of farmers not wearing PPE while mixing and applying pesticides.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…A study conducted in Palpa, Nepal observed that only 6% of farmers took complete protective measures like wearing protective clothing, hand gloves, goggles, masks, and taking bath immediately after application. (13) The findings from Bakhsh and colleagues another study in Pakistan on cotton farm workers revealed similar results as 40% young and 68% elder cotton pickers did not comply with safety measures. (23) In Egypt more than 97% of farmers not wearing PPE while mixing and applying pesticides.…”
Section: Discussionmentioning
confidence: 70%
“…(19) The similar result was reported in Turkey and in Nepal that not a single farmer in their studies received training on pesticide use. (20,13) A study conducted in Greece revealed a positive relation between training and the farmer's knowledge of pesticide use, safety behaviour, and beliefs in pesticide hazard control. (21) Hence, training should be encouraged for all farmers in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most farmers perceive pesticides to be useful and safe for their health and the environment (Thapa et al, 2015). Some farmers do not even realize that certain health issues arise because of unsafe pesticide use Sharma et al, 2021), and medication for the illness associated with pesticide use is rare because the illnesses go unnoticed .…”
Section: Knowledge Synthesis and Discussionmentioning
confidence: 99%